Catalog of Aradidae (Hemiptera: Heteroptera) for the Neotropical Region - Del Carmen Coscarón, María; Contreras, Eugenia Fernanda (Zootaxa, 2012)
The Aradidae (Hemiptera) of the Neotropical Region are cataloged. A total of 80 genera and 509 species are listed togetherwith their synonyms. References are given to the original descriptions and the subsequent taxonomic position, the location of types and the geographic distribution. A comprehensive bibliography is provided.